2010
DOI: 10.1007/s10734-010-9396-5
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of international student mobility flows: an empirical study on the Erasmus programme

Abstract: The Erasmus Programme for higher education students is supposed to play an important socio-economic role within Europe. Erasmus student mobility flows have reached a relevant level of two million since 1987, boosted in recent years by the enlargement of the programme to eastern countries. Thereafter, it seems that flows have staggered. In this context, the article analyses the determinants of Erasmus student mobility establishing relevant hypotheses, which arise from the migration theory and gravity models. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(127 citation statements)
references
References 20 publications
(27 reference statements)
9
90
1
5
Order By: Relevance
“…Serving a quarter of a million students each year, this is the European 'success story' (Rivza & Teichler, 2007, p. 464) with regard to short-term student mobility. Its underlying ideas and rationales (Papatsiba, 2006), conditions (Rodríquez González et al, 2011) and professional outcomes (Bracht et al, 2006) have been investigated. Further, analyses of the socio-economic status of mobile citizens in general and mobile students in particular find that mobility is highly correlated with social background variables (see Pineda et al, 2008;Souto-Otero, 2008;Mau & Büttner, 2010;Brooks & Waters, 2011;Finger, 2011;Lörz & Krawietz, 2011).…”
Section: Mobility On the Rise?mentioning
confidence: 99%
“…Serving a quarter of a million students each year, this is the European 'success story' (Rivza & Teichler, 2007, p. 464) with regard to short-term student mobility. Its underlying ideas and rationales (Papatsiba, 2006), conditions (Rodríquez González et al, 2011) and professional outcomes (Bracht et al, 2006) have been investigated. Further, analyses of the socio-economic status of mobile citizens in general and mobile students in particular find that mobility is highly correlated with social background variables (see Pineda et al, 2008;Souto-Otero, 2008;Mau & Büttner, 2010;Brooks & Waters, 2011;Finger, 2011;Lörz & Krawietz, 2011).…”
Section: Mobility On the Rise?mentioning
confidence: 99%
“…For instance, Rodríguez González et al [43] focused on country size, the cost of living, distance, the educational background, university quality, the host country language, and climate. These factors are found to be significant for mobility decisions.…”
Section: Theoretical Model Developmentmentioning
confidence: 99%
“…Evaluation performed by INCHER in 2006 examined the professional value of ERASMUS mobility, and the results indicated that the mobility programmes had provided students with increased professional skills and a higher likelihood with working abroad also later in their professional careers (Bracht et al, 2006). Other research has indicated that while Erasmus provides funding for study abroad periods, financial constraints still play a role in decisions, as well as family educational background, country size, distance, university quality, language, country size and climate (Rodríguez González, Bustillo Mesanza, & Mariel, 2011).…”
Section: Eu Initiatives In Higher Educationmentioning
confidence: 99%